Development of augmented reality-based E-Cergam and students’ understanding of information texts - Rahmawati, Niken Dwi; Purwati, Panca Dewi (Indonesian Research Journal in Education |IRJE|, 2025)
This research aims to describe (1) the development design, (2) determine the feasibility, and (3) determine the effectiveness of the Ketep Pass picture book learning media based on augmented reality. This research uses the ADDIE model of research and development (R&D). The research population was 31 students: 9 students for small group trials (class IV A) and 22 students for large group trials (class IV B) of SD Negeri Banyuroto 1 Magelang, Central Java. Data was collected through interviews, observations, questionnaires, tests, and documentation, with qualitative and quantitative analysis. The media development design integrates local wisdom content into information texts. The validation results show that this media has a high feasibility level. The results of the paired sample t-test confirm significant differences before and after using the developed media. Then, the N-Gain test on the small and large group showed a high category which prove that the Ketep Pass picture book media based on augmented reality is efficacious in improving students' reading comprehension.